A marcação a mercado nos fundos de investimento em 2002: uma tentativa de alongamento da dívida pública brasileira - Holanda, Fernanda Heloisa da Cruz (2006)
The public debt has always been a concerning subject in the Brazilian economy, representing a significant percentage of the GDP since the decade of 1980. Although some economic plans and many attempts to improve and to change the profile of the debt, little success was achieved. Brazilian public debt reached the total of more than R$ 1 trillion in 2006. Because of that, in 2002, the government tried to modify the public debt profile again. Although the economic and political scenario was turbulent in 2002, the Brazilian government tried to modify the public debt profile. The Central Bank introduced the mark to market in the investment funds and, additionally, it made a tie-in sale of securities tied to the exchange with securities post-fixed. That brought great volatileness to the financial market and to investment funds, where most of ordinary people invest their money. The objective of this paper is to analyze the mark to market process in the securities of public debt and, consequently, in investment funds, focusing how the economic authorities introduced this new way of accounting, the goal they wanted to achieve, the market reaction, and also how this initiative reflected on the investment funds and, mainly on the small investors. We analyzed the net debt of the public sector, using the Central Bank and National Treasure time series. We also analyzed economic and politic events that preceded the mark to market and the economic conjuncture it was implemented. The analysis of the mark to market was done based in the data from ANDIMA, São Paulo Stock Exchange and Central Bank. The verified results had indicated the great volatileness of the investment funds. They have never registered similar variation, mainly for the ordinary investors. The episode of the mark to market showed how difficult is to change the public debt without causing great variations in the market where the securities are negotiated